Studies in Asian social development / edited by Ratna Dutta and P.C. Joshi - "Dutta, Ratna.(ed.)" (Bombay, 1971)
The present volume consists of ten papers dealing with some aspects of the changing social situation in Asia in the contemporary period. The basic concern of these studies is with problems and processes of develop- ment in selected countries of the Asian region. They are focussed spe- cially on land reform and agrarian change, on employment situation and change in professions, on religion and politics, and on national integration.
Keywords: Sociology